Design of a charging station for electric vehicles in Singapore - Tan, Zhi Wei. (2012)
Despite the low environmental impact and high energy efficiency, electric vehicles (EV) have not been largely recognized by people. One of the reasons is the absence of charging infrastructure. Lithium-ion battery used for electric vehicles promotes fast charging due to its high energy density and low internal resistance. Also, it will significantly enhance the accessibility of using EV if charging infrastructure is effectively-equipped.